Sexual function and obesity - Larsen, S.H; Wagner, G; Heitmann, B.L (International Journal of Obesity, 2007)
Objective: To review the literature on the relationship between obesity and sexual function. Method: A search in the medical literature from 1966 and onwards was carried out through Medline and Embase for publications on obesity, in combination with Medical Subject Heading words related to sexual function and dysfunction. Comments: Four prospective and seven cross-sectional studies were found describing association between obesity and erectile dysfunction (ED). One cross-sectional study was found describing obesity and female sexual dysfunction (FSD). The prospective studies on ED all demonstrated a direct association and so did five of the seven cross-sectional studies. The single FSD study did not find any relationship. Eight intervention studies on weight loss and sexual difficulties were identified. All included few individuals and results were mixed even if most indicated an increase of sexual activity among both men and women after weight loss intervention. Conclusion: Support for the assumption that obesity is associated with ED was found in both prospective and cross-sectional studies. FSD was not adequately described in the literature and prospective studies are needed here. Results from weight loss intervention studies are less conclusive, but also point toward improvement in sexual dysfunction with reduced weight.